REPRESENTASI KEKERASAN TERHADAP PEREMPUAN DALAM MEDIA ONLINE DI MAKASSAR: ANALISIS WICANA KRITIS SARA MILLS - Hukmi, Arif (BASINDO : jurnal kajian bahasa, sastra Indonesia, dan pembelajarannya, 2024)
This study aims to reveal and analyze the representation of violence against women in online news published in the Fajar Daily in 2024. Adopting a critical discourse analysis approach developed by Sara Mills, this study explores how violence against women is represented, constructed, and reported by online media, particularly Harian Fajar. This research method involves collecting samples of online news related to violence against women, then conducting text analysis using a critical discourse analysis framework. The results of this analysis are expected to provide an in-depth understanding of how online media affects public perceptions of violence against women and the narrative construction contained in the news. The research also has implications for gender advocacy and the role of the media in supporting women's empowerment and addressing discrimination and violence against them.Keywords: Violence against Women, Critical Discourse Analysis, Online Reporting